AN ANALYZIS OF ENGLISH NATIONAL EXAM: Test of English Proficiency for Student - Uswatunnisa Uswatunnisa (ELT Worldwide: Journal of English Language Teaching, 2020)
The National Exam of 2019 is still one of the absorbed issues to discuss. The researcher brings the issue up because in a couple of years there might be no more National Exam since the new minister is more likely to believe that Exams are conventional so the issue of abolishing it is heating up again. The National Exam has become a standard evaluation made by the government for every school level. The English exam is an English proficiency test for students. Yet, the test consists of listening and reading comprehension only. The objectives of the study are to find out whether the questions tested are appropriate with the qualifications, criteria, and the goals of each competence. Then, the researcher analyzed the error of each question. The researchers applied the general method in assessing the English test referring to the Hakuta and Jacks (2009) guidelines. The researcher applied descriptive qualitative as the research design. The test is focused more on cognitive skills, especially in reading skills. The students are taught all four language skills in schools and are expected to be superior to all of them at least. The researcher finds some errors in the test such as the test directions are unclear. Then, the questions are compiled disorderly and the amount of questions for each language competence is not equal. The test is not appropriate with the language learning objectives and so does with the language mastery demands.